Association of California Mastitis Test Scores with Intramammary Infection Status in Lactating Dairy Cows Admitted to a Veterinary Teaching Hospital. (9th December 2017) - Kandeel, S.A.; Morin, D.E.; Calloway, C.D.; Constable, P.D.
Abstract : Background: Subclinical mastitis is of concern in veterinary hospitals because contagious mastitis pathogens might be unknowingly transmitted to susceptible cows and then back to their farm of origin. Objectives: To evaluate the California mastitis test (CMT) as an indicator of intramammary infection (IMI) in lactating dairy cows admitted to a veterinary hospital. Animals: A total of 139 admissions of 128 lactating dairy cows admitted to the University of Illinois Veterinary Teaching Hospital over a 2‐year period. Methods: A retrospective study with a convenience sample was conducted. Medical records of cows with CMT results and milk culture results for the day of admission were reviewed. Breed, age, season, maximum CMT score for the 4 quarters, maximum CMT score difference, and clinical diagnosis were evaluated as predictors of IMI by the chi‐square test and stepwise logistic regression. Results: An IMI was identified in 51% of quarters. For cows admitted without evidence of clinical mastitis, the sensitivity of a CMT score ≥trace in predicting an IMI on a quarter or cow basis was 0.45 and 0.68, respectively. The distributions of maximal quarter CMT score and the maximum difference in quarter CMT score for cows without evidence of clinical mastitis did not differ ( P  = 0.28, P  = 0.84, respectively) for cows with and without IMI. Stepwise logistic regression did not identify significant predictors of IMI in cows without clinical mastitis. Conclusions: Lactating dairy cattle admitted to a veterinary hospital should be managed as if they have an IMI, even in the absence of clinical mastitis.